The national symbols in the publications of O. Akchokrakly (comments on the article “The matter of the Flag”) - Refat Abduzhemilev (Крымское историческое обозрение)
The article offers the Russian translation of the publication by the Crimean Tatar scientist and writer O. Akchokrakly (1878–1938) entitled “Bayrak Meselesi” (“The matter of the Flag”) from No. 108 of the “Millet” newspaper in 1917. The preface contains a summary of the translated work: the choice of the colour of the Tatar flag by Muslim Military Council, the blue colour of the ancient Turks, the display of Islamic colours on the flag, tarak-tamga and dragons as attributes of the flag. In the historical survey the stages in the use of the official state symbols by the Crimean Tatars are traced: horsetail (bunchuk) in the Golden Horde, standards and horsetails in the Crimean Khanate, the Muslim sanjak (standard), the flag during the Crimean People’s Republic in the time of the Second Kurultay. The considerable attention is paid to the colour symbolism on the standards. In the article were also noted the fragments from the Crimean Tatar chronicles “Tarikh-i Sahib Geray Khan”, “Tarikh-i Islam Geray Khan”, “Tarikh-i Mehmed Geray”, in the descriptions of which horsetail and sanjak had taken place.